Genetic Diversity of Native Pig in Thailand Using Microsatellite Analysis - Wanee Chaiwatanasin; Somchai Chantsavang; Srisuwan Chomchai; Neramit Sookmanee; Sompoch Tabchareon (Agriculture and Natural Resources, 2002)
Fifteen microsatellite loci were analyzed in 49 random individuals to characterize the genetic variability of native pig breed (native pig from the north, 22 and native pig from the northeast, 27) in Thailand. Mean numbers of allele per locus, mean numbers of shared allele per locus and average gene diversity per locus were 8.60, 4.27 and 0.7742, respectively. Polymorphism information content (PIC), observed and expected heterozygosity of native pig from the north (0.5630, 0.4496 and 0.6003, respectively) were less than the values of native pig from the northeast (0.7439, 0.5570 and 0.7743, respectively). Nei’standard genetic distance between native pig from the north and native pig from the northeast was 0.5510. These results indicated that genetic diversity of native pig from the northeast was higher than that from the north.